Dissociable Effects of Tryptophan Supplementation on Negative Feedback Sensitivity and Reversal Learning - Thirkettle, Martin; Barker, Laura-Marie; Gallagher, Thomas; Nayeb, Nazgol; Aquili, Luca (Frontiers in Behavioral Neuroscience, 2019)
Serotonin has been shown to modulate probabilistic reversal learning (PRL) and negative feedback sensitivity (NFS) in both animal and human studies. Whilst these two measures are tightly coupled, some studies have suggested that these may be mediated by independent mechanisms; the former, representing perseveration and cognitive flexibility, and the latter measuring the ability to maintain a response set (win-stay) at the expense of lose-shift behaviour when occasional misleading feedback has been presented. Here, we tested this hypothesis in 44 healthy participants who were administered tryptophan (22 placebo, 22 tryptophan), a presynaptic precursor to serotonin. We found a dissociable effect of tryptophan supplementation on PRL/NFS. Specifically, tryptophan administration increased NFS compared to the placebo group but had no effect on PRL. We discuss these findings in relation to presynaptic and postsynaptic mechanisms, receptor specificity, and dosage and with a particular focus on the acute tryptophan depletion (ATD) procedures.